IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION NEWS ITEM TEXT BY USING GRAPHIC ORGANIZER - Marginingsih Marginingsih; Moh Muhtarom; Sundari Sundari; Norkhairi Ahmad (Universitas Duta Bangsa Surakarta, 2026)
Reading comprehension is essential for non-language students in English for Specific Purposes (ESP) to access domain-specific knowledge, yet many face challenges with news item texts due to their complex structure and limited exposure to journalistic content, leading to high reading anxiety and low comprehension scores. This study aimed to evaluate the effectiveness of graphic organizers in enhancing reading comprehension of news item texts and to assess student perceptions in an ESP context. Employing a quantitative quasi-experimental one-group pretest-posttest design, the research involved 120 second-semester students from Universitas Duta Bangsa and Universitas Dharma AUB, Surakarta, using reading comprehension tests and a perception questionnaire. Results showed a significant score increase (mean = 15.76; p < 0.001; N-Gain = 0.42, moderate), with a positive shift in score categories and reduced variance. Students reported high satisfaction (mean = 3.24) with the ease, clarity, and engagement of graphic organizers. These findings highlight graphic organizers as effective visual scaffolding tools, enhancing cognitive and emotional engagement, and suggest their integration into ESP pedagogy to improve academic reading outcomes for non-language learners across disciplines.